An Essential Role of Mitochondrial α-Ketoglutarate Dehydrogenase E2 in the Basal Immune Response Against Bacterial Pathogens in Tomato - Ma, Qiaomei; Liu, Yaru; Fang, Hanmo; Wang, Ping; Ahammed, Golam Jalal; Zai, Wenshan; Shi, Kai (Frontiers in Plant Science, 2020)
Plants intensely modulate respiration when pathogens attack, but the function of mitochondrial respiration-related genes in plant–bacteria interaction is largely unclear. Here, the functions of α-ketoglutarate dehydrogenase (α-kGDH) E2 subunit and alternative oxidase (AOX) were investigated in the interaction between tomato and the virulent bacterial pathogen Pseudomonas syringae pv. tomato DC3000 (Pst). Pst inoculation suppressed the transcript abundance of α-kGDH E2, but enhanced AOX expression and salicylic acid (SA) accumulation. Gene silencing and transient overexpression approaches revealed that plant susceptibility to Pst was significantly reduced by silencing α-kGDH E2 in tomato, but increased by overexpressing α-kGDH E2 in Nicotiana benthamiana, whereas silencing or overexpressing of AOX1a did not affect plant defense. Moreover, silencing octanoyltransferase (LIP2), engaged in the lipoylation of α-kGDH E2, significantly reduced disease susceptibility and hydrogen peroxide accumulation. Use of transgenic NahG tomato plants that cannot accumulate SA as well as the exogenous SA application experiment evidenced that α-kGDH E2 acts downstream of SA defense pathway. These results demonstrate tomato α-kGDH E2 plays a negative role in plant basal defense against Pst in an AOX-independent pathway but was associated with lipoylation and SA defense pathways. The findings help to elucidate the mechanisms of mitochondria-involved plant basal immunity.